Pengaruh Kualitas Kehidupan Kerja dan Kompetensi Terhadap Kinerja Dengan Kepuasan Kerja Sebdagai Variabel Intervening Pada Perawat Rumah Sakit Umum Daerah Bahteramas Provinsi Sulawesi Tenggara - Rizky Maharani Rustam; Endro Sukotjo; Sinarwaty Sinarwaty (Pascasarjana Universitas Halu Oleo, 2023)
This study aims to: 1) examine the influences quality of work life on performance, 2) analyze the influences of competence on performance, 3) analyze the impacts of quality of work life on job satisfaction, 4) analyze the impacts of competence on job satisfaction, 5) analyze the impacts of job satisfaction on performance.6) analyzing job satisfaction that mediate the effect quality of work life on performance, 7) analyze job satisfaction that mediate the effect of incompetence on performance. This study uses quantitative methods and questionnaires for the data collection process. Furthermore, the population of this study were all nurses from Bahteramas Regional General Hospital in Southeast Sulawesi Province. For the sampling technique, the researcher used multistage sampling with the total of 174 samples obtained using the determination of the sample according to Ferdinand (2006). The researcher used Warp Partial Least Squares (PLS) for analyzing the data in this study. The results of the study showed that: 1) the quality of work life had a positive and insignificant effect on performance, 2) competence had a positive and significant effect on performance, 3) the quality of work life had a positive and significant effect on job satisfaction, 4) competence had a significant effect on job satisfaction, 5) job satisfaction had a positive and significant effect on performance, 6) job satisfaction had a positive and significant effect on mediating the effect of work life quality on performance, 7) job satisfaction had a positive and significant effect on mediating the influence of competence on performance